Dietary influences on production, stoichiometry and decomposition of particulate wastes from shredders. (21st November 2014) - Halvorson, Halvor M.; Fuller, Chris; Entrekin, Sally A.; Evans‐White, Michelle A.
Summary Aquatic shredders produce large quantities of fine particulate organic matter (FPOM) as fragments and egesta, but the significance of shredder FPOM as a pathway of consumer‐mediated nutrient transformation remains understudied. We fed the stream shredders Pycnopsyche lepida, Lepidostoma sp. and Tipula abdominalis oak or maple litter conditioned under contrasting phosphorus concentrations to produce gradients in dietary carbon:phosphorus (C:P) and carbon:nitrogen (C:N) content (range = 850–4480 and 30–49 by moles, respectively). We measured total production and stoichiometry of FPOM to estimate particulate N and P release rates, compared resultant rates to those of P excretion and measured microbial decomposition of FPOM. FPOM production was lowest for Lepidostoma and higher for Tipula and Pycnopsyche; FPOM production by Tipula increased on higher‐nutrient diets. The C:P, C:N and N:P of FPOM from Pycnopsyche and Tipula often diverged from diet stoichiometry depending on litter type, and rates of particulate N and P release by shredders were greater with increasing nutrient content of the diet. Shredders fed high‐nutrient diets produced FPOM with greater microbial decomposition rates, although these trends differed between litter types. Bottom‐up changes in litter type and nutrient content may modify production, stoichiometry and decomposition of FPOM from shredders, and shredder‐mediated nutrient transformations may differ across shredder species.